Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Hotel Kara Guest House Sragen - Arifin, Zainal; , Basworo Dibyo, S.E, M.Si (2015)
The hotel is a service business accommodation in which there are elements of service , comfort , lodging and facilities needed for those who wants a means of lodging for the interests of families and liburan.penelitian aims to mengetahuiapakah dimension in the quality of services that is tangible , reliability , responsiveness , assurance , and emphaty impact on customer satisfaction and analyzing the factors most dominant in customer satisfaction affect kara hotel guest house in Sragen. Population in this research is consumers who use services kara hotel guest house in sragen .The sample in take as many as 60 respondents using non-probability technique the sampling method of accidental with the approach of sampling , namely the determination of the sampling method of technique based on chance meeting with researchers sample can be used as if it were viewed suitable Berdasarkan hasil pengujian melalui hasil analisis regresi liniear berganda diperoleh persamaan sebagai berikut :Y= 53,378 + 〖0,365X〗_1 + 0,358X_2+0,376X_3 + 〖0,630X〗_4+ 0,397X_5 . Dengan uji t menghasilkan thitung untuk variabel tangible sebesar 3,937 , reliabilitysebesar 3,885 , responsiveness sebesar 3,707,assurance sebesar7,765dan emphaty sebesar 5,975. Dengan demikian tampak bahwa nilai koefisien regresi variabel assurancemerupakan nilai koefisien variabel tertingi. Based on the results through the results of testing regression analysis double liniear obtained an equation as follows: y = 53,378 + 0,365x1 + 0,358x2 + 0,376x3 + 0,630x4 + 0,397x5 .With the tangible t produce thitung for variables tangible 3.937; reliability 3,885, responsiveness 3,707 , emphaty 7,765, emphaty 5,975.Thus it appears that the value of the regression coefficient assurancemerupakan the value of the coefficients tertingi variable variable Key Words :Tangibles, Reability, Responsiveness, Assurance, Emphaty and Custumer Satisfaction